STUDY OF JUDICIAL TRANSFORMATIONS IN THE STRUCTURE OF MODERN SCIENTIFIC KNOWLEDGE - Valentina M. Bolshakova (Russian Studies in Law and Politics)
The paper examines judicial transformations as a subject of knowledge in modern post-non-classical science. The increased attention of researchers to the study of the dynamics of the existence of the judicial system, the features of its hierarchical structure and functioning is traditionally popular for theoretical and applied legal work. In modern times, the judicial system operates in the conditions of modernization of various spheres of public life, the growth of social threats and political contradictions, the instability of the financial and economic situation and the need to staff the positions of judges with qualified and experienced personnel. Solving the problems of improving judicial activity is possible by overcoming the negative impact of these factors, which will ensure the qualitative development of the domestic judiciary. The main scientific results of the work include the fact that it summarizes the ideas about judicial transformations in the judiciary and judicial sphere. The materials of the study and the main conclusions are addressed to persons conducting scientific research on the problems of the judiciary and legal proceedings.